Electrochemical performance of SrSc0.2Co0.8O 3-d cathode on Sm0.2Ce0.8O1.9 electrolyte for low temperature SOFCs - Zhou, W.; An, B.; Ran, R.; Shao, Zongping (The Electrochemical Society, Inc, 2009)
The application of the SrSc0.2Co0.8O 3-d (SScC) perovskite as a cathode material on the Sm0.2 Ce0.8 O1.9 electrolyte for reduced-temperature-operation solid oxide fuel cells (SOFCs) was investigated in detail. Oxygen reduction reaction (ORR) on the SScC cathode was studied by two-electrode impedance, three-electrode-polarization test, and four-probe dc conductivity measurement at various temperatures, oxygen partial pressures, and polarization values. The oxygen nonstoichiometry of SScC is 0.552 at 500°C. An extremely high oxygen vacancy concentration in the SScC lattice decreased the resistances from oxygen adsorption, dissociation, and diffusion processes at low temperatures. This subsequently improved the electrochemical performance of the cathode. The polarization overpotential is only -110 mV for the SScC cathode at the current density of -1070 mA cm-2 at 600°C in air. The kinetics of ORR on the SScC cathode was studied by ac impedance, which revealed that the charge-transfer process was the rate-determining step due to the extremely low electrical conductivity of SScC. © 2009 The Electrochemical Society.